2017
DOI: 10.1155/2017/1609575
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Epigenetics of Hepatocellular Carcinoma

Abstract: Hepatocellular Carcinoma (HCC) is one of the most predominant malignancies with high fatality rate. This deadly cancer is rising at an alarming rate because it is quite resistant to radio- and chemotherapy. Different epigenetic mechanisms such as histone modifications, DNA methylation, chromatin remodeling, and expression of noncoding RNAs drive the cell proliferation, invasion, metastasis, initiation, progression, and development of HCC. These epigenetic alterations because of potential reversibility open way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 167 publications
0
61
0
1
Order By: Relevance
“…In recent decades, non-coding genes contributing to epigenetic regulations have been verified to associate with the occurrence and progression of HCC (Wahid et al 2017). Dating back to ten years ago, researchers performed miRNA microarray assay to classify specific diagnostic miRNAs for HCC (Murakami et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, non-coding genes contributing to epigenetic regulations have been verified to associate with the occurrence and progression of HCC (Wahid et al 2017). Dating back to ten years ago, researchers performed miRNA microarray assay to classify specific diagnostic miRNAs for HCC (Murakami et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a set of miRNAs was deregulated in HCC, and some of them play important roles in the carcinogenesis and progression of HCC [18][19][20][21]. In addition, some of these deregulated miRNAs can be used as diagnostic or prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, HCC mortality rate is very high because it is quite resistant to radio-and chemotherapy [5]. Thus, new treatment choices are critically required.…”
Section: Introductionmentioning
confidence: 99%